The Edge Metric Dimension of the Comb Product of a Cycle and a Graph with a Dominant Vertex - Abdilla Nurul Azisah Mn; Hasmawati Hasmawati; Budi Nurwahyu; Nurdin Hinding (GTA Research Group, Univ. Newcastle, Indonesian Combinatorics Society and ITB, 2026)
In this paper, we determine the edge metric dimension of the comb product of a cycle graph and a simple graph containing a dominant vertex. This result generalizes previous findings on the edge metric dimension of the comb product of a cycle and a complete graph. We show that the edge metric dimension of Cn ▷ D, where D is a simple graph with a dominant vertex, equals the product of the order of Cn and the order of D reduced by two.